2000
DOI: 10.1080/713754386
|View full text |Cite
|
Sign up to set email alerts
|

Organisation of left and right hand movement in a prehension task: A longitudinal study from 20 to 32 weeks

Abstract: The organisation of reaching movements was studied longitudinally (every two weeks) in infants aged from 20 to 32 weeks, in order to detect possible differences between the two hands. An object was presented on a table, at a reachable distance, and four trials were retained. Analysis of left and right hand movements was performed, frame-by-frame, on video images obtained from two cameras. Three body points were considered: the elbow, the wrist, and the major finger for drawing the profile of the movement. Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 15 publications
4
16
0
3
Order By: Relevance
“…Os resultados indicaram que enquanto a preferência manual foi bastante inconsistente em idades precoces, a análise cinemática revelou um perfil de desempenho caracterizado por poucas unidades de movimento e movimentos mais retilíneos no alcançar realizado com o braço direito em comparação com o esquerdo. Esse padrão foi observado para a maioria dos bebês em todas as idades avaliadas (ver também Morange-Majoux, Peze, & Bloch, 2000). Achados de pesquisa adicionais têm mostrado uma vantagem de desempenho na execução com a mão direita em tarefas requisitando altas frequências de movimento em diferentes idades durante a infância (Bruml, 1972;Denckla, 1974;Fagard, 1987;Ingram, 1975) e ações manipulativas (Caplan & Kinsbourne, 1976;Petrie & Peters, 1980).…”
Section: Suporte à Participação Filogenética Na Formação Da Lateralidadeunclassified
“…Os resultados indicaram que enquanto a preferência manual foi bastante inconsistente em idades precoces, a análise cinemática revelou um perfil de desempenho caracterizado por poucas unidades de movimento e movimentos mais retilíneos no alcançar realizado com o braço direito em comparação com o esquerdo. Esse padrão foi observado para a maioria dos bebês em todas as idades avaliadas (ver também Morange-Majoux, Peze, & Bloch, 2000). Achados de pesquisa adicionais têm mostrado uma vantagem de desempenho na execução com a mão direita em tarefas requisitando altas frequências de movimento em diferentes idades durante a infância (Bruml, 1972;Denckla, 1974;Fagard, 1987;Ingram, 1975) e ações manipulativas (Caplan & Kinsbourne, 1976;Petrie & Peters, 1980).…”
Section: Suporte à Participação Filogenética Na Formação Da Lateralidadeunclassified
“…Analysis of toy manipulation (Petrie & Peters, 1980) and of reaching movements (Morange-Majoux, Peze, & Bloch, 2000) in infants have indicated that asymmetric performance in manual actions are detectable early in motor development. The results by Petrie and Peters indicated that infants squeezed the toy harder and held it longer when grasping with the right hand, while in the analysis of reaching Morange-Majoux et al, observed a more rectilinear motion when movements were performed with the right in comparison with the left arm.…”
Section: Introductionmentioning
confidence: 99%
“…Hand differences in reaching kinematics and spatio-temporal organization (Corbetta & Thelen, 1999; Morange Majoux, Peze, & Bloch, 2000) may modulate the level of difficulty associated with reaching for moving objects depending on whether the ipsilateral hand is the preferred hand or not. If the reaching movement performed by the ipsilateral hand is not fast enough to capture an object in the ipsilateral hemifield, then the infant may need either to cross the midline or to switch to the contralateral hand.…”
Section: Introductionmentioning
confidence: 99%